2014
DOI: 10.1590/1516-635x1604375-380
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between endogen amylin hormone and some hormonal, biochemical and bone parameters in pullets

Abstract: The objective of this study was to assess the correlations of amylin (a pancreatic polypeptide hormone) with some hormonal, biochemical and bone parameters in pullets. Forty 18-week-old pullets were used. Plasma amylin, CT (calcitonin), 1,25 (OH)2 vitamin D (1,25 dihydroxycholecalciferol ), serum osteocalcin, glucose, ALP (alkaline phosphatase), cholesterol, and triglycerides, as well as weight, length and total volume of tibiotarsi were measured. Plasma amylin concentration was negatively correlated with seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(35 reference statements)
2
0
0
Order By: Relevance
“…With regard to the external quality of the fresh eggs, the present study showed that amylin injection increased eggshell thickness (P<0.05), and this finding is in agreement with our previous study (Guzel et al, 2009). Even though numerous studies have described a calciotropic (calcium-regulating) effect of amylinomimetic agents including human amylin (Wu et al, 2018) and rat amylin (Davey et al, 2006), information about the effects of amylin in hens is limited with very little literature (Guzel et al, 2009;Guzel and Gunes, 2014). Laying hens lose their structural bone in the late laying period, leading to cortical thining and osteoporosis, causing welfare problems and economic loses (Bain et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With regard to the external quality of the fresh eggs, the present study showed that amylin injection increased eggshell thickness (P<0.05), and this finding is in agreement with our previous study (Guzel et al, 2009). Even though numerous studies have described a calciotropic (calcium-regulating) effect of amylinomimetic agents including human amylin (Wu et al, 2018) and rat amylin (Davey et al, 2006), information about the effects of amylin in hens is limited with very little literature (Guzel et al, 2009;Guzel and Gunes, 2014). Laying hens lose their structural bone in the late laying period, leading to cortical thining and osteoporosis, causing welfare problems and economic loses (Bain et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with this, our previous work have reported that amylin injection in laying hens leads to an increase in bone Ca level, cortical width, and eggshell thickness (Guzel et al, 2009). In our other study, we showed that endogenous amylin appears to interact with calcitonin hormone levels in pullets (Guzel and Gunes, 2014). However, it is not exactly known whether amylin also influences external and internal egg quality traits, and this is addressed in the present study.…”
Section: Introductionsupporting
confidence: 89%